Catheter Ablation of Ventricular Arrhythmias Originating From the Region of DGCV-AIV via a Swartz Sheath Support Approach - Cheng Zheng; Wei-Qian Lin; Yao-Ji Wang; Fang-Zhou Lv; Qi-Qi Jin; Jin Li; Jia-Feng Lin (Frontiers in Cardiovascular Medicine, 2021)
Aims: This study aimed to investigate an appropriate catheter manipulation approach for ventricular arrhythmias (VAs) originating from the left ventricular epicardium adjacent to the transitional area from the great cardiac vein to the anterior interventricular vein (DGCV-AIV).Methods: A total of 123 patients with DGCV-AIV VAs were retrospectively analyzed. All these patients underwent routine mapping and ablation by conventional approach [Non-Swartz sheath support (NS) approach] firstly. In the situation of the distal portion of the coronary venous system (CVS) not being accessed or a good target site not being obtained, the Swartz sheath support (SS) approach was attempted alternatively. If this still failed, the hydrophilic coated guidewire and left coronary angiographic catheter-guided deep engagement of Swartz sheath in GCV to support ablation catheter was performed.Results: A total of 103 VAs (103/123, 83.74%) were successfully eliminated in DGCV-AIV. By NS approach, the tip of the catheter reached DGCV in 39.84% VAs (49/123), reached target sites in 35.87% VAs (44/123), and achieved successful ablation in 30.89% VAs (38/123), which was significantly lower than by SS approach (88.61% (70/79), 84.81 % (67/79), and 75.95% (60/79), P < 0.05). There were no significant differences in complication occurrence between the NS approach and the SS approach (4/123, 3.25% vs. 7/79, 8.86%, p > 0.05). The angle between DGCV and AIV <83° indicated an inaccessible AIV by catheter tip with a predictive value of 94.5%. Width/height of coronary venous system>0.69 more favored a SS approach with a predictive value of 87%.Conclusion: For radiofrequency catheter ablation (RFCA) of VAs arising from DGCV-AIV, the SS approach facilitates the catheter tip to achieve target sites and contributes to a successful ablation.